2016
DOI: 10.1186/s13030-016-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal bloating is the most bothersome symptom in irritable bowel syndrome with constipation (IBS-C): a large population-based Internet survey in Japan

Abstract: BackgroundAbdominal bloating is a common symptom in patients with irritable bowel syndrome with constipation (IBS-C). However, it is not included among the required items in the Rome III diagnostic criteria for IBS. Little is known about an impact of abdominal bloating seen in patients with IBS-C. Using a large population-based sample, the aim of the present study was to investigate what is the most bothersome symptom in subjects with IBS-C.MethodsAn Internet survey of 30,000 adults drawn from the general publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 33 publications
2
59
1
Order By: Relevance
“…While the aim of the previous study was to identify the most bothersome symptom in patients with IBS-C [13], the aim of the present study was to investigate the prevalence of IBS-C symptoms by gender and age. Details of the survey are described in the previous report [13].…”
Section: Methodsmentioning
confidence: 99%
“…While the aim of the previous study was to identify the most bothersome symptom in patients with IBS-C [13], the aim of the present study was to investigate the prevalence of IBS-C symptoms by gender and age. Details of the survey are described in the previous report [13].…”
Section: Methodsmentioning
confidence: 99%
“…Similar data come from the Far East: thus, in a Japanese online survey, Kanazawa et al reported that up to 30% of healthy subjects and almost all IBS patients may be affected by bloating [34].…”
Section: Bloating In Ibsmentioning
confidence: 60%
“…In the majority of studies, the prevalence is higher in constipation-predominant IBS patients compared with diarrheapredominant IBS patients, while some investigators found no relation of bloating to any of IBS subtype [35,36]. A strong correlation between the severity of abdominal bloating and the degree of abdominal distension only in patients with constipation predominant IBS suggest that the pathophysiology may be different between subtypes of IBS [34,37]. Using plethysmography it has been demonstrated that most patients with abdominal distension also report abdominal bloating and that patients with bloating alone have lower sensory thresholds in the rectum compared to healthy subjects, since those with abdominal bloating and distension have normal or higher sensory thresholds [38].…”
Section: Bloating In Ibsmentioning
confidence: 99%
See 2 more Smart Citations